Metal–Organic Frameworks Derived Plasmonic Catalyst with Full Spectral Response for Photoelectrochemical Water Splitting Enhancement. Issue 5 (19th August 2021) - Li, Chuanping; Li, Shuoren; Hang, Tianxiang; Guo, Feifei; Zhu, Xian-Dong; Liu, Tian-Fu
Abstract : Water splitting through photoelectrochemical (PEC) catalytic reaction holds significant promise for energy conversion. However, the low energy‐storage efficiency severely hinders the practical applications owing to the narrow spectral absorption and adverse charge recombination. Herein, a plasmon‐enhanced catalyst, integrating metal–organic frameworks (MOFs)‐derived Cd0.8 Zn0.2 S with Ag/Au hollow porous nanoshells (Ag/Au HPNSs), is rationally designed to afford Ag/Au HPNS‐Cd0.8 Zn0.2 S nanoshells (Ag/Au HPNS‐Cd0.8 Zn0.2 S NSs), which extends the absorption range from the ultraviolet to the near‐infrared region. The PEC performance shows that the photocurrent of the anode exhibits an approx. tenfold enhancement and full spectral response compared with the intrinsic ZIF‐8 dodecahedrons. More detailed exploration and theoretical simulations find that the MOFs‐derived Cd0.8 Zn0.2 S, with a high dielectric constant, can markedly prevent the decay of the plasmon fringing field and broaden the interaction range of the electromagnetic field. Such a synergistic effect finally improves the charge separation efficiency and results in the superior PEC performance of the photoanode. This work offers a new method for the construction of efficient PEC catalysts and provides new insights into the understanding of the plasmonic effect on catalytic reactions. Abstract : A metal–organic framework‐derived plasmonic catalyst (Ag/Au HPNS‐Cd0.8 Zn0.2 S NS) is rationally designed and fabricated. Mechanism exploration and theoretical calculation indicate that the full spectral response and prevented decay of the plasmon fringing field can significantly improve the light absorption ability and charge separation efficiency of the catalyst, finally resulting in excellent photoelectrochemical water oxidation performance.